Laser directed dynamic hydrogen template deposition of porous Pt@Ag networks. (20th October 2017) - Wolf, Mario; Caro, Jürgen; Feldhoff, Armin; Steinbach, Frank; Schulz-Ruhtenberg, Malte; Lange, Karsten
Abstract: A porous Ag network has been deposited on laser structured Ni supports by using the dynamic hydrogen template deposition (DHTD) technique. For a better hydrogen evolution, a 10 nm Pt layer has been sputtered on the Ni supports before Ag deposition. In a subsequent step, the Ag network has been modified by electrochemical Pt deposition in a replacement reaction forming a porous Pt@Ag network. Different Pt species are formed at different positions of the Ag network: Pure Pt on top and Ag1 Pt1 alloy at the interface between the Ag network and the deposited Pt film. Laser structuring the substrate in advance can facilitate mass transport, especially for the galvanic Pt replacement reaction, and improves the performance of the electrode. As a result, the performance of the Pt@Ag network on laser structured electrodes is significantly higher compared to a non-structured electrode.